Reconceptualizing Self-Affirmation With the Trigger and Channel Framework: Lessons From the Health Domain. (August 2019) - Ferrer, Rebecca A.; Cohen, Geoffrey L.
Self-affirmation—a theory-based technique to affirm the adaptive adequacy of the self—can promote positive behavior change and adaptive outcomes, although effects are variable. We extend a novel framework (Trigger and Channel), proposing three conditions that facilitate self-affirmation-induced behavior change: (a) presence of psychological threat, (b) presence of resources to foster change, and (c) timeliness of the self-affirmation with respect to threat and resources. Using health behavior as a focus, we present meta-analytic evidence demonstrating that when these conditions are met, self-affirmation acts as a psychological trigger into a positive channel of resources that facilitate behavior change. The presence of a timely threat and the availability of timely resources independently predicted larger self-affirmation effects on behavior change, and the two interacted synergistically to predict still larger effects. The results illustrate the conditionality of self-affirmation effects and offer guidelines for when, where, and for whom self-affirmation will be most effective.